Robert Parris Moses : a life in civil rights and leadership at the grassroots - Visser-Maessen, Laura (UNC Press law publications., 2016)
"This new biography casts Moses in a new light, revealing him as a far more strategic, calculating, and hands-on organizer than in previous portrayals of him as an idealist and saintly figure."--Provided by publisher